Polymer Properties Determination For Designing Chemical Flooding - Sugihardjo Sugihardjo (Scientific Contributions Oil and Gas, 2011)
Waterflooding became the standard practice in many reservoirs formation in petroleum industries, the strengths and weaknesses of the methods were quite well established. In particular, the inefficiency of the waterflood oil displacement mechanism as a result of either an unfavorable mobility ratio or heterogeneity was largely identified. Therefore, chemicals injections as the improvement displacement processes had been proposed to support petroleum industries to recover the production of oil. Chemical injection normally consists of alkaline, surfactant, and polymer (ASP). They could be injected as standalone fluid or mixture of fluids; it depends upon the injection fluid design appropriate for particular field. Polymer solution could be prepared for mixtures of injection fluid and or as chase fluid injection which is injected behind surfactant or ASP. The main function of polymer solution primarily is to viscosity the injection water as a mobility control. This work is proposed to determine the important polymer properties which are suitable for mobility control in such EOR plan in the particular field. This field is sandstone reservoir with oil gravity of 23 to 26oAPI and viscosity of 3cp at 90oC. Two kinds of polymers have been chosen such as: HPAM-1 and HPAM-2 and subject to be tested for the properties characteristic. Intensive works have been done to evaluate the bulk polymer properties at laboratory scale which include rheology, filtration, thermal stability, retention/adsorption, and injectivity or permeability reduction tests. The results indicated that HPAM-1 polymer is suitable for injection fluid design for Zone-B while HPAM-2 for Zone-A.